Electronic transport properties of graphene/Al2O3 (0001) interface - Gusmão, M. S.; Ghosh, Angsula [UNESP]; Frota, H. O. (Elsevier, 2018)
The electronic structure and transport properties of a single layer of graphene (Gr) on α-Al2O3 surface are studied using the density functional theory (DFT). We present three models that take into account the atom at the termination of the alumina surface: a) Al atoms, with the center of the Gr hexagon directly over an Al atom; b) Al atoms, with a carbon directly positioned above an Al atom; c) oxygen atoms. Two processes of geometric optimization were used: (i) All the atoms of the supercell were allowed to move in accordance with the BFGS quasi-Newton algorithm; (ii) The atoms of the three topmost layers of the α-Al2O3 (0001) slab, including the C atoms, were allowed to move, whereas the atoms of the remaining layers were frozen in their respective atomic bulk positions. The first two models preserve qualitatively the electronic structure of the pristine Gr using the geometric optimization process (i) whereas, in the third model this structure was lost due to a significant charge transfer between the carbon and oxygen atoms irrespective of the optimization procedure. However, models (a) and (b) with the optimization (ii) reveal a p-type semiconducting behavior.
Keywords: Alumina; DFT; Graphene; Transport properties